Risk Factors for Urinary Tract Infections in Children with Hematuria in the Emergency Department - Bei-Cyuan Guo; Chun-Yu Chen; Wun-Yan Huang; Wen-Ya Lin; Ying-Ju Chen; Tai-An Lee; Mao-Jen Lin; Han-Ping Wu (MDPI AG, 2024)
Introduction: Hematuria is a worrisome symptom in children and is sometimes associated with urinary tract infections (UTIs). This study aimed to identify useful clinical factors that can predict UTIs in hematuria patients without pyuria in the pediatric emergency department (ED). Methods: We retrospectively recruited patients with hematuria from the pediatric ED. Clinical symptoms, urine biochemistry and microscopic examination results, and blood laboratory tests were analyzed to identify the predictors of UTIs. Patients were divided into the verbal group (age ≥ 2 years) and non-verbal group (age < 2 years) for identifying predictors of UTIs. Causes of hematuria were also investigated. Results: A total of 161 patients with hematuria without pyuria were evaluated. Among symptoms, dysuria was significantly correlated with UTIs. Regarding urine biochemistry data, urine esterase and urine protein > 30 mg/dl were found to be significant parameters for predicting UTIs, while urine esterase and urine nitrite showed significant differences in children with age < 2 years. In the urine microscopic examinations, urine red blood cells (RBC) > 373/µL in children aged ≥ 2 years and urine RBC > 8/µL in children aged < 2 years were associated with UTIs. In addition, UTIs and urinary tract stones were found to be the top two causes of hematuria. Conclusions: Dysuria, urine esterase, urine nitrite, and urine protein may be useful parameters for predicting UTIs in pediatric patients with hematuria but no pyuria in the ED. In addition, a UTI was the most commonly identified etiology of hematuria without pyuria, followed by urinary tract stones.